Comparative study of pain in women submitted to conventional laparoscopic cholecystectomy versus single-port laparoscopic cholecystectomy - Terra Júnior,Júverson Alves (2017)
Abstract Purpose: To evaluate postoperative pain in patients submitted to conventional laparoscopic cholecystectomy with four ports versus single-port laparoscopic cholecystectomy with only one port. Methods: Twenty-one patients were included in the conventional laparoscopic cholecystectomy group and 19 other patients in the single-port laparoscopic cholecystectomy group. A VAS was used for the assessment of postoperative pain at three time points. Differences were considered statistically significant when p<0.05. Results: Intergroup analysis showed no significant difference in VAS scores between the conventional laparoscopic cholecystectomy and single-port laparoscopic cholecystectomy groups at any of the time points studied. Conclusion: This study found no significant difference in postoperative pain between the two groups.